ANALISIS KONFLIK SOSIAL DALAM NOVEL DOMPET AYAH SEPATU IBU KARYA J. S KHAIREN DAN IMPLEMENTASINYA SEBAGAI BAHAN AJAR SASTRA DI SMA/MA - Firly Al'zha; Bhakti Prima Findiga Hermuttaqien; Fithry Muthmainnah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the low learning outcomes of fourth-grade students in the IPAS subject at UPT SD Negeri 77 Pinrang. Based on initial observations, only 8 out of 18 students achieved scores above the Learning Objectives Achievement Criteria (KKTP). This problem was caused by the lack of variation in the learning models used by the teacher, the dominance of the lecture method, and the limited opportunities for students to think critically and engage actively in the learning process. Additionally, students were not accustomed to working in groups, lacked confidence in expressing their opinions, and were more accustomed to receiving direct answers from the teacher. This research aims to improve student learning outcomes through the implementation of the Problem-Based Learning (PBL) model. This study employed Classroom Action Research (CAR) with a qualitative approach conducted in two cycles. Data collection techniques included observation, tests, and documentation. The results showed an improvement in student learning outcomes and learning activities after the implementation of the PBL model. Thus, the implementation of the Problem-Based Learning (PBL) model effectively enhances IPAS learning outcomes among fourth-grade students at UPT SD Negeri 77 Pinrang.